2000
DOI: 10.5032/jae.2000.02025
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Selected Preservice Agricultural Teacher Education Programs in the United States

Abstract: The researchers surveyed department heads of purposefully selected agricultural teacher education programs to determine the curricular structure of agricultural teacher education in the United States. Nominations ofprograms to examine were sought from members of the profession. Graduation checklists and course syllabi for all professional agricultural education courses were analyzed. The authors concluded that programs vary greatly across the country. Courses on teaching methods and program and curriculum plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 4 publications
1
46
0
Order By: Relevance
“…In addition, there is no literature regarding the intended interactions to accomplish these purposes. Such observations caused McLean and Camp (2000) to recommend further study to determine the commonalities among agricultural teacher education programs and to question what type of experiences preservice teachers encounter in EFE (Swortzel, 1999).…”
Section: Theoretical Framework Of Efementioning
confidence: 99%
“…In addition, there is no literature regarding the intended interactions to accomplish these purposes. Such observations caused McLean and Camp (2000) to recommend further study to determine the commonalities among agricultural teacher education programs and to question what type of experiences preservice teachers encounter in EFE (Swortzel, 1999).…”
Section: Theoretical Framework Of Efementioning
confidence: 99%
“…To ensure its effectiveness, EFE should be aligned with the entire teacher preparation program (Little & Robinson, 1997). McLean and Camp (1998) stated that the call for reform of agricultural teacher education preparation has gained momentum in the last 15 years. This momentum could be due in part to the impact of EFE in preservice teacher education.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, agriculture teacher preparation programs do not spend an equal amount of time instructing preservice teachers on SAE when compared to classroom/laboratory instruction and FFA (McLean & Camp, 2000). Sequentially, this has led preservice teachers to report a lower level of importance towards SAE program utilization as compared to the other major components of SBAE (Joerger, 2002).…”
mentioning
confidence: 99%
“…McLean and Camp (2000) conducted a study of 10 preservice agriculture teacher preparation programs and found that every program reported teaching SAE to their preservice teachers. However, the researchers found that three teacher preparation programs offered SAE specific courses to preservice agriculture teachers.…”
mentioning
confidence: 99%
See 1 more Smart Citation